PENGARUH KOMPENSASI DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PADA PT ERA MULIA ABADI SEJAHTERA DI MALANG - Udi Kusuma; Pompong Budi Setiadi; Sri Rahayu (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to determine the effect of compensation and career development on employee performance. This research was conducted on employees at PT Era Mulia Abadi Sejahtera in Malang, East Java. The research method used in this research is descriptive by using quantitative methods. This study uses primary data, namely the distribution of questionnaires by taking employee respondents at PT Era Mulia Abadi Sejahtera in Malang, East Java. This study uses a sample of the total population of the number of employees in the office. The analytical method used is multiple regression analysis which is processed using the SPSS application. The results of this study indicate that the variables of compensation and career development have a positive effect on employee performance. And the variables of compensation and career development simultaneously affect employee performance.